Resilience of international students during a global pandemic: An Australian context - Udah, Hyacinth; Gatwiri , Kathomi; Francis, Abraham (Journal of International Students, 2024)
The COVID-19 pandemic posed additional challenges for international students in Australia, affecting their academic, social, and personal wellbeing. In this article, we examine how international students in North Queensland (NQ) responded to these challenges and their resilience coping mechanisms. Using a mixed methods approach, we collected and analysed data from students who reported significant isolation, loneliness, financial and mental health challenges. Our findings showed that international students utilise different resilience strategies to adapt, cope and survive during times of crisis. In light of the challenges and opportunities that international students face in their academic journey, we argue that higher education institutions have a responsibility to develop and implement effective strategies to foster the resilience of this diverse group of learners. Such a commitment can also contribute to the internationalisation of higher education and international students’ retention, which are important goals for many higher education institutions in the globalised world.